Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.2196/19770
|View full text |Cite
|
Sign up to set email alerts
|

A Community-Developed, Web-Based Mobile App Intervention Addressing Social Work and Legal Needs of Black Sexual Minority Men Living With HIV: Protocol for a Randomized Comparison Trial

Abstract: Background Black sexual minority men (BSMM) are disproportionately affected by HIV. Los Angeles County (LAC) carries a substantial burden of the HIV epidemic in California. Negative effects of both psychosocial and structural barriers highlight the timely need to increase HIV treatment among BSMM. Successful HIV interventions based on social media and mobile phone technology have been demonstrated. This protocol describes LINX LA, a study that tests LINX, a web-based mobile app that provides tailor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The latter point is especially important given the emphasis in recent articles on community-engagement as one of the most promising and essential routes to EHE for people of color in the US [66,73 && ]. Notable examples of effective community-based collaborations include the integration of services provided by community-based pharmacists with those of medical providers to improve retention in care, rates of viral suppression, and adherence to antiretroviral medications among persons with HIV (PWHIV) [68][69][70]; community-engaged development of mobile HIV prevention apps for Black women [e.g., [71]] and Black sexual minority men; clinic-based strategies to improve care outcomes among PLWH experiencing homelessness and unstable housing [72], and concept mapping of multilevel resilience resources among adult Black PLWH in the Southern US [73 && ]. Recognizing the invaluable role of communitybased stakeholders in implementing EHE [66,74] and the need for 'multifactorial approach[es] accounting for the social, cultural, economic, and environmental factors that drive transmission of HIV' [74],…”
Section: National Responses To the Hiv Epidemicmentioning
confidence: 99%
“…The latter point is especially important given the emphasis in recent articles on community-engagement as one of the most promising and essential routes to EHE for people of color in the US [66,73 && ]. Notable examples of effective community-based collaborations include the integration of services provided by community-based pharmacists with those of medical providers to improve retention in care, rates of viral suppression, and adherence to antiretroviral medications among persons with HIV (PWHIV) [68][69][70]; community-engaged development of mobile HIV prevention apps for Black women [e.g., [71]] and Black sexual minority men; clinic-based strategies to improve care outcomes among PLWH experiencing homelessness and unstable housing [72], and concept mapping of multilevel resilience resources among adult Black PLWH in the Southern US [73 && ]. Recognizing the invaluable role of communitybased stakeholders in implementing EHE [66,74] and the need for 'multifactorial approach[es] accounting for the social, cultural, economic, and environmental factors that drive transmission of HIV' [74],…”
Section: National Responses To the Hiv Epidemicmentioning
confidence: 99%
“…Data for these analyses were derived from a community-developed, web-based mobile application designed to address the social work and legal needs of Black sexual minority men living with HIV in Los Angeles County, described in detail elsewhere (Ochoa et al, 2021). Briefly, Black sexual minority men living with HIV aged 18 years old and above who self-identified as Black/African American and living with HIV and who did not identify as heterosexual were recruited into a randomized comparison trial of an mHealth intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Data for this study come from self-reported responses to a cross-sectional baseline interview from LINX LA, a prospective, randomized comparison trial of a web-based mobile application, which is described in detail elsewhere. 38 Participants (N = 124) were recruited using a variety of in-person and virtual strategies, including flyers at HIV and Lesbian, Gay, Bisexual, and Transgender-friendly clinics and postings on social media platforms. To be eligible for the study, participants had to meet the following criteria: (1) be at least 18 years or older; (2) identify as male individual; (3) identify as Black or African American; (4) identify as gay, bisexual, or another sexual minority; (5) own a smartphone; (6) be living with HIV; (7) reside in Los Angeles County; and (8) be able to provide informed consent.…”
Section: Methodsmentioning
confidence: 99%